2015
DOI: 10.1002/2014wr016150
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multiple scales of hydraulic conductivity measurements in training image-based stochastic models

Abstract: Hydraulic conductivity is one of the most critical and at the same time one of the most uncertain parameters in many groundwater models. One problem commonly faced is that the data are usually not collected at the same scale as the discretized elements used in a numerical model. Moreover, it is common that different types of hydraulic conductivity measurements, corresponding to different spatial scales, coexist in a studied domain, which have to be integrated simultaneously. Here we address this issue in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…One of the most influential parameters in groundwater simulation is hydraulic conductivity (K), which is a soil property that measures the ability of soil to transmit fluid through pore spaces and fractures [1] (e.g., the ratio of velocity to hydraulic gradient). Previous studies [2][3][4][5] have demonstrated that hydrogeological parameters, such as transmissivity and hydraulic conductivity, exhibit log-normal distributions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most influential parameters in groundwater simulation is hydraulic conductivity (K), which is a soil property that measures the ability of soil to transmit fluid through pore spaces and fractures [1] (e.g., the ratio of velocity to hydraulic gradient). Previous studies [2][3][4][5] have demonstrated that hydrogeological parameters, such as transmissivity and hydraulic conductivity, exhibit log-normal distributions.…”
Section: Introductionmentioning
confidence: 99%
“…However, though hydraulic conductivity in soil and rock exhibits large spatial heterogeneity, with likely variations of several orders of magnitude within a short distance [7,8], only a small number of measurements can be made due to the prohibitively expensive cost. It is thus suggested that hydraulic conductivity should be addressed within a stochastic framework, and the uncertainty should be quantified in groundwater simulations in multiple aquifers [1,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations